The effects of l-arginine on urinary nitric oxide metabolites and renal lipid peroxidation in cisplatin treated rats [Sisplatin Uygulanmis Ratlarda idrar Nitrik Oksit Metabolitleri ve Böbrek Lipid Peroksidasyonu Üzerine L-Arjininin Etkisi] - (:unkn) unknown (My University, 2009)
Increase of lipid peroxidation and glutathione (GSH) depletion in kidney tissues have been observed in rats with cisplatin-(CDDP) induced nephrotoxicity. This investigation elucidates the role of L-arginine, the substrate of nitric oxide synthase (NOS), on renal injury, lipid peroxidation and urinary excretion of nitrite (NO2-)+ nitrate (NO3-) in rats with CDDP induced renal failure. CDDP (3 mg/kg, once a day) was injected intraperitoneally for 5 days. In subgroups, daily L-arginine (0.2g/kg) or NG -nitro-L-arginine methyl ester (L-NAME) (NOS inhibitor, 20 mg/kg) were administrated intraperitonally 1 hour prior to CDDP treatment. Treatment with CDDP resulted in significant increase plasma creatinine (Cr), urea levels, daily urine volume, urinary gamma glutamyl transferase (GGT) levels and significant decrease creatinine clearance and urinary NO2-+ NO3- excretion. Intraperitoneal administration of L-arginine in the low dose prevented the CDDP induced elevation of plasma Cr and urea levels. When compared with controls, CDDP administration resulted in increased lipid peroxidation and decreased GSH levels in the kidney; L-arginine reversed these effects. In addition, pretreatment of L-arginine was effective in the normalization of daily urine volume and urinary excretion of NO2-+ NO3-. On the other hand, the administration of L-NAME resulted in no protection agonist CDDP-induced renal damage. The findings of this study suggest that intraperitoneal L-arginine administration can prevent the CDDP-induced renal damage by a mechanism which involves the production of NO.
Keywords: Cisplatin; L-arginine; Lipid peroxidation; Urinary nitrate and nitrite